Neuroplasticity and functional reorganization of language in patients with arteriovenous malformations: insights from neuroimaging and clinical interventions - Yuan, Jialong; Niu, Hongchuan; Lei, Chengxu; Xu, Ruichen; Liu, Yutong; Yuan, Kexin; Zou, Linru; He, Shihao; Zhao, Yuanli (Frontiers in Human Neuroscience, 2025)
Patients with arteriovenous malformations (AVMs) located in the functional area of speech often exhibit language dysfunction, and neuroplasticity allows the brain of some patients to regain speech through functional reorganization. Exploring the mechanism of AVMs-induced reorganization of language function is important for understanding neuroplasticity and improving clinical intervention strategies. This review systematically searched and analyzed the research literature in related fields in recent years, covering data from neuroimaging, functional magnetic resonance imaging (fMRI), and clinical case studies. By integrating these evidences, the phenomenon of functional reorganization within non-verbal functional areas and its influencing factors in patients with AVMs were assessed. It concluded that functional reorganization of language due to AVMs is a manifestation of a high degree of neurological plasticity and that understanding this process has important implications for neurosurgical planning and postoperative rehabilitation of patients. Future research should continue to explore the mechanisms of functional reorganization in the brain and work to develop new diagnostic tools and therapeutic approaches to improve the rate of recovery of language function in patients with AVMs.